"Adaptive pathways" to drug authorisation: adapting to industry?. (16th August 2016) - Davis, Courtney; Lexchin, Joel; Jefferson, Tom; Gøtzsche, Peter; McKee, Martin
Abstract : Evidence for benefits to patients and public health of adaptive pathways is lacking or contradictory, say Courtney Davis and colleagues